Manejo da fertirrigação em solo salinizado para produção de rúcula (Eruca sativa) - Torres, Marcia Batista (2022)
With the estimated increase in irrigated areas affected by salts in the world, strategies to minimize adverse effects and maintain agricultural yield in these regions are necessary, such as strict control of the use of fertilizers applied through fertigation. Therefore, the aim this work was to determine the development of arugula in saline soil under different fertigation strategies. The experimental design was in randomized blocks in a 3x5 factorial scheme with four replications. The treatments consisted of five levels of soil salinity (ECes = 0.57; 1.3; 2.3; 3.3; 4.3 dS m-1) and three different doses of fertilization via fertigation (F1= 100%, F2=50% and F3=25%, of the recommended amount of N, K2O and P2O5), with a frequency of two days. The cultivation was carried out in beds and in a protected environment, having as substrate a soil characterized as Red Yellow Latosol, salinized with the aid of calibration curves between the amount of salts applied and ECes. The following variables for the arugula crop were analyzed in two production cycles: number of leaves, plant height (at 15, 22 and 30 days after transplanting), leaf area, shoot fresh mass, shoot dry mass, plant moisture content, gas exchange, relative chlorophyll content and nutritional analysis of the area part (N, P, K, Ca, S, Mg, Cu, Fe, Mn, Na and Zn). For evaluation purposes, regression analysis was used for the quantitative factors and the mean test for the qualitative factors. In the 1st cycle, it was observed that the variable leaf area presented a significant response with quadratic adjustment for the interaction of salinity with fertigation factor, at concentrations of 50% and 25% and linear model at 100% concentration. According to the data, a decrease of 37.43 cm2 of leaf area was observed for each unit increase of ECes in the F1 treatment. According to the data, a decrease of 37.43 cm2 of leaf area was observed for each unit increase of ECes in the F1 treatment. For the variable fresh mass of the part area, in the 1st production cycle, the model adjusted for the interaction between ECes and fertigation was linear for F1 (100%) and F2 (50%), which showed decreases of 2.857 g plant-1 and 2.579 g plant-1 respectively, for each unit increment of ECes, while for F3 a quadratic model was used. The research results allowed us to conclude that ECes values greater than 2.3 dS m-1 impair the development and consequent yield of the arugula crop, regardless of the fertigation strategy used, thus pointing to a strategy with less use of fertilizers.